TRAINING OF MANAGEMENT STAFF IN THE VILLAGE OF SOVIET UKRAINE AT THE BEGINNING OF THE THIRTIES IN THE XX-TH CENTURY - Мандрик, Я. І.; Пуйда, Р. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article there has been analyzed the system of administrative personnel education for rural economy in Soviet Ukraine within 1930-tieth. It has been studied the work of agricultural higher educational establishments and vocational schools; great attention has been paid to the investigation of different courses and schools. The assignment system of the above-mentioned personnel in villages has been shown.